2015
DOI: 10.14260/jemds/2015/1822
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Effect of Ormeloxifene in Management of Perimenopausal Dysfunctional Uterine Bleeding

Abstract: OBJECTIVE:To study the effect of ormeloxifene in dysfunctional uterine bleeding in premenopausal age group by measuring menstrual blood loss by PBAC score, effect on blood hemoglobin levels and effect on endometrial thickness. METHODS: 35 cases of DUB of age 40 years and above coming to Gynecological OPD were recruited for study after applying exclusion criteria. 60 mg of Ormeloxifene was given twice a week for 3 months and then once a week for 1 month. Patients were followed-up at 1, 3 and 4 months of therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The nonresponsiveness with ormeloxifene was variable from 3.3-16.7% in other studies. 25,27 Maximum women had reported amenorrhea (25.3%) as common side effect of drug in our study which was comparable with study of Agarwal et al, 30 which reported among 60 women (28.3%) and Kanchan et al, 25 (32.6%) among 50 women, which was welcoming for the age near menopause, whereas it was lower incidence compared to study by Anjum S et al, 31 (68.7%). Studies by other authors also mentioned about minor side effects not severe enough to the point of stopping ormeloxifene.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The nonresponsiveness with ormeloxifene was variable from 3.3-16.7% in other studies. 25,27 Maximum women had reported amenorrhea (25.3%) as common side effect of drug in our study which was comparable with study of Agarwal et al, 30 which reported among 60 women (28.3%) and Kanchan et al, 25 (32.6%) among 50 women, which was welcoming for the age near menopause, whereas it was lower incidence compared to study by Anjum S et al, 31 (68.7%). Studies by other authors also mentioned about minor side effects not severe enough to the point of stopping ormeloxifene.…”
Section: Discussionsupporting
confidence: 85%
“…Studies by other authors also mentioned about minor side effects not severe enough to the point of stopping ormeloxifene. 19,30 Ormeloxifene therapy among women with AUB/DUB has been provided since 2000 and it can be started from anytime of cycle for HMB as endometrial haemostatic agent working within 48 hours of use. It is of advantage among menopause transition women being cardio-protective and prevents osteoporosis, compared to other drugs as well as budget friendly.…”
Section: Discussionmentioning
confidence: 99%